Fusarium spp. and associated mycotoxins in South African maize - Joubert, Sonia-Mari (University of the Free State, 2020)
Maize is an important staple food and feed crop in South Africa. This crop is however threatened by pathogens/pathogen complexes such as the Fusarium graminearum species complex (FGSC), the F. oxysporum species complex (FOSC) and F. verticillioides. These pathogens not only cause a decrease in grain yield and quality but may also produce mycotoxins, the most prevalent being deoxynivalenol (DON), nivalenol (NIV), zearalenone (ZEA) and fumonisins (FUM). This study was conceptualised because our understanding of Fusarium spp.-maize interactions is often limited to ear rots. Thus, this study consisted of five diverse chapters, which together gives a better understanding of the interaction between maize and Fusarium spp.. In Chapter 2 the North West province, in conjunction with, crop rotations, had the highest concentration of FGSC, FOSC and F. verticillioides. Unexpectedly, maize/wheat and maize monoculture did not contain the highest concentration of fungi. FGSC and F. verticillioides favours stalk tissue whereas FOSC favours roots. As expected, no-till fields favours pathogen/pathogenic complex disease but this is limited to certain tissues. Dryland fields favoured pathogen/pathogenic complex infection. ZEA and FUM were found in the majority of samples but FUM did not exceed the MTL set by the government whereas ZEA did. DON was less abundant but greatly exceeded the MTL during the third season. This suggests that although mycotoxins are season dependent there is a possibility that levels that could cause harm to humans and animals may be exceeded. This study enhances our knowledge of the influence of agricultural practices on these three Fusarium spp.. It also clearly indicates the importance of appropriate agricultural practices in reducing the risk of significant infection levels. In Chapter 3 the effect of abiotic and biotic factors on prematurely senescing plants in the Northern Cape was determined. It was observed that five nutrients impacted FGSC target DNA concentrations and increased (PSA) or decreased (VGA) the plants susceptibility. Ca increased disease severity with a trend towards higher stem rot incidence, whereas Mg, Na, K and B decreased disease incidence by increasing overall plant health and decreasing disease incidence and severity by the various role they play in plant defence responses. It was also shown that during the soft dough stage maize is the most sensitive towards plant disease. Thus, it could be seen that poor soil nutrition (environment), coupled with a susceptible plant (soft dough stage) and significantly high FGSC target DNA concentrations in In1 and In2 of season 2012/13 (virulent pathogens) resulted in the PSAs in maize fields. In Chapter 4 mycotoxin translocation throughout maize plants has in the past been shown to be possible, however in this study translocation of DON, NIV and ZEA was not shown. This was attributed to either the inability of these mycotoxins to be translocated in maize, the conditions were not ideal for translocation, or the maize genotypes were not conducive to translocation. The possibility of FUM translocation has only been evaluated in maize seedlings from roots to the leaves. In this study it was shown that there is a possibility of FUM translocation but because of the trace amounts of FUM found this possibility could not be confirmed. Thus, mycotoxin translocation of DON, NIV and ZEA was not confirmed but the possibility of FUM translocation was shown. Chapter 5 the first to examine maize stalk defence responses. It was expected that PR-1 would be highly upregulated at each time-point in the resistant cultivar with limited induction in the susceptible cultivar. Instead PR-1 was initially supressed, between 0 – 48 hai, then induced 96 hai. This was attributed to the biotroph/necrotroph switch. It is hypothesised that PR-1 plays a role in F. boothii-maize stalk rot resistance. WRKY1 was only induced in the susceptible cultivar at 72 hai. It is hypothesised that WRKY1 does not play a role in F. boothii-maize stalk rot resistance but may be responsible for the susceptibility of PAN 6479. Although some assumptions could be made from this study, further analysis is required to gain a definitive understanding of maize defence responses toward FGSC. Controlling pathogens or pathogen complexes such as Fusarium spp. is extremely difficult as they are highly adaptive, complex and diverse. However, as our understanding of these fungi increases so do the strategies in containing infections. This study focused on the interaction between Fusarium spp. and maize. The findings of this study could contribute to the prediction of Fusarium spp. infection on maize, the reduction in Fusarium disease on maize, the adaption of farming practices, and crops with less mycotoxin contamination.
Thesis (Ph.D. (Plant Sciences))--University of the Free State, 2020
Keywords: Maize; Plant pathogens; Fusarium; Grain yield; Muycotoxins; Agriculture; Plant pathology